Kajian metode penentuan kekuatan momen retak tiang pancang spun pile - Candra Irawan; I Gusti Putu Raka; Priyo Suprobo (Institut Teknologi Sepuluh Nopember (ITS), 2020)
This paper describes the results of a study carried out experimentally on the determination of the moment strength ofspun pile piles. The methods used are visual observation, load-displacement curve evaluation, and tensile strain analysis. Theexperimental results show that a load of data taken is delayed between 3 and 9 % compared to the results based on loaddisplacement curve. Analysis results from the load-deflection curve is similar to the tensile strain reading in the PC bar. Atcrack, there exist a sudden jump in the tensile strain of the PC bar where at the same time the stiffness of the load-deflectioncurve was changed.